A model to optimize maintenance through implementing industry 4.0 technologies - Safaa Essalih; Zineb El Haouat; Mohamed Ramadany; Fatima Bennouna; Driss Amegouz (Heliyon)
Against the backdrop of the fourth industrial revolution, manufacturing companies seek to boost profits by incorporating the digital technologies of Industry 4.0. Maintenance has an important contribution to achieving production goals and system performance. It is a key element because it reduces machine downtime, thus improving the overall efficiency of production system equipment. Nevertheless, companies have encountered significant difficulties in shifting toward digital transformation including a lack of expertise, an inability to ensure a reasonable return on investment, a scarcity of skilled workers, and the absence of a standardized implementation approach. Despite existing studies, a comprehensive approach to integrate these technologies specifically within the maintenance function remains underexplored. This research aims to address this gap by conducting a comparative analysis of eleven methods previously proposed in the literature. The objective is to develop a generic model that facilitates the deployment of Industry 4.0 technologies into maintenance optimization. This unified model offers a structured framework for manufacturing firms to effectively integrate Industry 4.0, thereby enhancing their maintenance strategies.